Роль домену РН білка BCR у клітинних процесах, що визначають фенотип Ph`-позитивних мієлопроліферативних захворюваннях - Гур'янов, Д.С.; Лисецька, Т.Ю.; Антоненко, С.В.; Кравчук, І.В.; Телегеєв, Г.Д. (Фактори експериментальної еволюції організмів, 2014)
Aims. Three forms of fusion protein BCR/ABL differ by the presence or absence of PH and DH domains of BCR protein and cause different phenotypes of myeloproliferative disorders. To date, 23 proteins-candidates were identified as possible interaction partners of PH domain of BCR protein. Among them are different functional groups, such as cytoskeletal proteins, those involved in reorganization of cytoskeleton and clathrine-mediated endocytosys, matrix proteins and proteins involved in inhibition of proteolytic degradation. Therefore it is crucial to verify those interactions with more sensible and reliable methods as this will give clue to the functional differences, which lead to onset of different disorders. Methods. We used restriction enzyme-based ligation, coimmunoprecipitation and western-blot for creation of genetic constructs and verification of protein-protein interactions between PH domain of BCR and putative partners. Results. Different genetic constructs were created, that will be used for the expression of target sequences (USP1, CTTN, TUBB, KRT10, COL4A1) in bacterial and mammalian expression systems. Also we demonstrate that FBP17 protein interacts with PH domain in mammalian cell line 293T. Conclusions. Demonstrated interaction of PH domain and FBP17 shows its’ important role in endocytosis and related cytoskeleton organization. All derived genetic constructs will be used in future research to verify interaction of target sequences with PH domain of BCR by far-Western blot, coimmunoprecipitation and fluorescent microscopy. It will be important in the future to check whether full-length BCR/ABL p210 interacts with USP1, CTTN, TUBB, KRT10, COL4A1, and FBP17, to study how it affects their phosphorylation state, and to determine their localization in the cell.

Key words: chronic myelogenous leukemia, myeloproliferative disorders, BCR/ABL, endocytosis, cytoskeleton reorganization, proteasomal degradation.